1998
DOI: 10.1381/096089298765554485
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Technique of the Fobi-Pouch Operation for Obesity (The Transected Silastic Vertical Gastric Bypass)

Abstract: The Fobi-Pouch operation (FPO) for obesity is the product of clinical trials, more than 15 years of personal clinical experience and information gathered from publications, scientific meetings, and personal communications with other bariatric surgeons. The essence of the operation is the small vertical pouch (< 25 ml), an externally supported stoma, the interposed Roux-en-Y limb, the gastrostomy and the bypassed stomach marker to facilitate percutaneous transabdominal access to the bypassed segment. Patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 20 publications
0
33
0
5
Order By: Relevance
“…Patients scheduled to undergo bariatric surgery, the Roux- en-Y gastric bypass procedure according to Capella and Capella [28 ]and Fobi [29], were eligible for the study if they met the following entry criteria: age between 18 and 65 years; BMI ≥40 kg/m 2 or BMI ≥35 kg/m 2 with one or more severe comorbidities (diabetes mellitus, systemic arterial hypertension, coronary artery disease, OSAHS and/or severe degenerative arthropathy) [30,31,32,33]; coexisting moderate-severe OSAHS determined by polysomnography in the 6 months prior to surgery, combined with symptoms of excessive daytime somnolence, and at least one sustained non-surgical weight loss attempt with inadequate results. The patients were restudied 18 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Patients scheduled to undergo bariatric surgery, the Roux- en-Y gastric bypass procedure according to Capella and Capella [28 ]and Fobi [29], were eligible for the study if they met the following entry criteria: age between 18 and 65 years; BMI ≥40 kg/m 2 or BMI ≥35 kg/m 2 with one or more severe comorbidities (diabetes mellitus, systemic arterial hypertension, coronary artery disease, OSAHS and/or severe degenerative arthropathy) [30,31,32,33]; coexisting moderate-severe OSAHS determined by polysomnography in the 6 months prior to surgery, combined with symptoms of excessive daytime somnolence, and at least one sustained non-surgical weight loss attempt with inadequate results. The patients were restudied 18 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…All of the individuals who underwent surgery received an open-banded RYGB by the same surgical team using standardized methods (2,13) . The surgical technique involved the creation of a 30 mL gastric pouch, a 100 cm alimentary limb and a 50 cm biliopancreatic limb.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Concerning the gastroenterostomy, different techniques exist: hand-sewn, a stapler anastomosis with hand-sewn closure of the stapler openings or use of the CEE stapler, whereas the combined (stapled and hand-sewn) technique provides the lowest stricture rate [17]. Fobi uses the proximal part of the Roux limb as a serosal patch on the edge of the pouch to prevent leaks and gastro-gastric fistula [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that leaving the band led to better weight loss than removing it during the revisionary operation. The next consequent step in 1989 was the stapled banded gastric bypass as a primary procedure followed by the transected banded gastric bypass in 1992 by Fobi to reduce the risk of gastro-gastric fistulas [2,3]. This operation was initially performed with a temporary gastrostomy tube in the remnant stomach, which was expected to prevent acute gastric dilation and could be used as an alternative route for medication and fluid intake in the early postoperative phase [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation